Evaluation of Agriculture Instead of Natural Geographical Locations in Khorezm Region - Nazarov Husniddin Yoqubovich; Sulaymonov Navruzbek Gulmurod o’gli (Web of Journals Publishing, 2023)
In Mongolia, the ethnoecological views of the Uzbeks of the Fergana Valley with livestock were briefly analyzed based on scientific sources and ethnographic field inscriptions. Scientific conclusions on the ethnoecological views of Uzbeks in the Fergana Valley with livestock are presented in Magana.